Spiking SARS-CoV-2 antiviral immunity in the respiratory tract. Issue 2 (February 2023) - Silva-Sanchez, Aaron; Randall, Troy D.
Abstract: The COVID-19 pandemic enabled the successful launch of mRNA-based vaccines that, when given intramuscularly, elicit spike-specific antibodies and prevent severe disease, but do not promote mucosal immunity. New data suggest how to boost systemic immunity and elicit pulmonary immunity in a way that more effectively controls infection and impairs transmission.